Influence of integrated weed management on production and quality in muskmelon seed (Cucumis melo) - NISHA CHOPRA; N.K. CHOPRA; K.C. NAGAR; H. PRASHANTH BABU (Seed Research, 2026)
Field experiment was carried out during two spring summer seasons to find out the effect of integrated weed management on seed yield and quality in muskmelon. Lowest weed density, weed dry weight and highest weed control efficiency (95.8%) was recorded with glyphosate 1.0% + hoeing compared to alachlor @ 1.0 kg/ha and pendimethalin @ 1.0 lit/ha supplemented with one hand weeding. Glyphosate 1.0% + hoeing recorded significantly higher seed yield than alachlor @ 1.0 lit/ha and pendimethalin @ 1.0 lit/ha supplemented with one hand weeding. Significantly higher values of seed germination, seedling length, seedling dry weight and seedling vigour indices, whereas significantly lower values of electrical conductivity (0.265 and 0.220 mS/cm/g) were observed in glyphosate 1.0% + hoeing and polythene mulch (700 μ) compared to one hand weeding and weedy check (0.432 and 0.458 mS/cm/g), respectively.